A Strategy for Resolving Europe's Problem Loans - Aiyar, Shekhar (Staff Discussion Notes; Staff Discussion Notes ;, 2015)
Europe's banking system is weighed down by high levels of non-performing loans (NPLs), which are holding down credit growth and economic activity. This discussion note uses a new survey of European country authorities and banks to examine the structural obstacles that discourage banks from addressing their problem loans. A three pillared strategy is advocated to remedy the situation, comprising: (i) tightened supervisory policies, (ii) insolvency reforms, and (iii) the development of distressed debt markets.